Cannabis Neuropsychiatry and Its Effects on Brain and Behavior - Colizzi, Marco; Bhattacharyya, Sagnik (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Over the years, there has been increasing interest into the public health impact of cannabis use, especially by young adults. This follows the evidence of a growing prevalence of regular cannabis use worldwide, with approximately 200 million users. Recreational cannabis use, especially a frequent use of products with high levels of its main psychoactive ingredient delta-9-tetrahydrocannabinol (Δ 9-THC), can cause dependence and have transient and long-lasting detrimental mental health effects, also negatively impacting cognitive processing and brain function and metabolism. In regular users, the development of tolerance to some of the effects of cannabis, especially the pleasurable ones, may lead to progressively heavier use in order to obtain the same effects in terms of their intensity, with higher health risks. However, the Cannabis Sativa plant contains different chemicals with different potential effects. In this regard, cannabidiol has gained interest because of its potential therapeutic properties, in line with evidence that CBD and Δ9-THC may exhibit opposite effects at the cannabinoid receptor type 1 (CB1), Δ9-THC being a partial agonist and CBD an antagonist/inverse agonist. Different cannabinoids may modulate human brain function and behavior in different ways, with different risk-benefit profiles.